Influence of digestion procedures on the determination of rare earth elements in peat and plant samples by USN-ICP-MS - Krachler, Michael; Mohl, Carola; Emons, Hendrik; Shotyk, William (Journal of analytical atomic spectrometry, 2002)
Analytical procedures for the determination of rare earth elements (REE) in 250 mg aliquots of difficult-to-digest peat and plant matrices by ICP-MS were developed. Three different pressurised digestion approaches were tested for this purpose, namely (i) closed vessel acid digestion on a hot-plate at 180 °C, (ii) digestion in a microwave high pressure autoclave at a temperature of 240 °C and (iii) high pressure ashing (HPA) at a temperature of 320 °C. Acid mixtures for digestion contained concentrated nitric acid (3-5 ml) alone or additions of hydrofluoric acid (HF) or tetrafluoroboric acid (HBF4) at volumes of 0.05-1.0 ml. The selection of appropriate volumes of HF or HBF4 was identified as a critical step in obtaining accurate results. For several reasons, HBF4 is preferred in comparison with the normally used addition of HF for the destruction of siliceous matter in the samples investigated. The optimum acid mixture consisted of 3 ml of HNO3 and 0.1 ml of HBF4. High sample throughput (40 samples simultaneously in about 2 h) favours the microwave autoclave over the other two digestion systems. An ultrasonic nebuliser (USN) with membrane desolvation used for sample introduction reduced the spectral interferences originating from oxide formation of lighter REE and Ba to a negligible extent. Internal standardisation with Rh and Re proved to be essential for obtaining correct results. In this way, all REE could be reliably quantified by USN-ICP-MS without applying any mathematical correction equations. The accuracy of the optimised procedures was assessed by the determination of REE in digests of the certified reference material GBW 07602 Bush Branches and Leaves and of the candidate reference material CRM 670 Aquatic Plant. The developed analytical procedures were applied to the determination of REE in two different peat matrices. Results for these peat samples obtained by USN-ICP-MS showed good agreement with INAA values. Strong fractionation of REE caused by the addition of HF or HBF4 in excess, known as lanthanide contraction, could be experimentally established, except for europium, which revealed a different behaviour.
Gesehen am 05.10.2020